Hak Veto Menteri Tenaga Kerja dan Transmigrasi dan Perlindungan Hukum bagi Rakyat dalam Penyelesaian Perselisihan Perburuhan - mila karmila adi (Jurnal Hukum IUS QUIA IUSTUM, 2003)
There is a govemment's intervention in the Labour Dispute Resolution Law, called Veto, that is belong to the Minister of The Employment and Transmigration. The Veto influences the parties'right to have a just decision in their labour dispute resolution process because it can be made by the Minister's will. The Veto should be diminished or even wiped out from the process because it only gives a political decision that influence the juridical decision of the Central Institution (Panitia Penyelesaian Perselisihan Perburuhan Pusat/Panitia Pusat.